Pendamping Penggunaan Media Gambar untuk Menciptakan Pembelajaran Bahasa Inggris Yang Aktif, Inovatif, dan Kreatif di Kelas IV SDK Mbomba - Siprianus See; Maria Natasya Bela Ritan; Maria Magdalena Ese Burong; Maria Yustina Bhena; Maria Fransiskan Susan Dagomes (Lembaga Pengembangan Kinerja Dosen, 2025)
In the teaching and learning process, teachers have the task of encouraging guiding and providing learning facilities for students to achieve their goals. On of the factors that influences interest in learning is teacher creativity. This study aims to determine teacher Creativity in improving learning at SDK MBOMBA This study takes a qualitative approach. One of the Teachers creative abilities in learning is creating aids in the form of family cards. The descriptive nature of this study makes teacher creativity very involved. Data collection in this study includes observation, documentation studies and analysis. The results of this study indicate that there are four key components in the development of this qualitative study related to teacher creativity in improving the quality of SDK MBOMBA learning, such as teacher creativity in understanding learning materials that will be taught creativity in managing the classroom environment, creativity in using various learning methods and teacher creativity in use of learning media.